Ocular syphilis: Case Series (2000–2015) from Two Tertiary Care Centers in Montreal - Vadboncoeur, Julie (Open Forum Infect Dis, 2017)
BACKGROUND: In the past 15 years, a recrudescence of syphilis was observed in Canada, along with a surge in ocular syphilis cases. Without treatment, ocular syphilis can have serious consequences potentially leading to blindness. Our goal was to describe the demographics, clinical presentations, proportion of co-infection with HIV, treatments and visual outcomes of ocular syphilis cases. METHODS: Patients with a confirmed positive syphilis serology between 2000 and 2015 were identified through the reference laboratory database. A retrospective chart review was performed for those who visited the ophthalmology clinic of Hôpital Maisonneuve-Rosemont or Hôpital Notre-Dame to identify ocular syphilis cases. RESULTS: Among the 119 patients (174 eyes) identified (2.5% of the population screened), 80% were male; of which 63% were MSM. Mean presenting logMAR visual acuity was 0.70 (20/100 Snellen) and unilateral ocular involvement occurred in 54%. Ocular manifestations included interstitial keratitis (24 eyes), anterior uveitis (37 eyes), intermediate uveitis (17 eyes), posterior uveitis (31 eyes), panuveitis (27 eyes), isolated optic nerve involvement (25 eyes), and others (12 eyes) including VI nerve palsy, scleritis, and episcleritis. Cerebrospinal fluid (CSF) examination was done in 65 (55%) patients. Of those, VDRL was positive in 14 (22%) patients; white blood cells and proteins were elevated in, respectively, 28 (43%) and 39 (60%) of patients. HIV status was unknown in 39 (33%) patients; among those whose serology were performed (or previous status was known), 38 (48%) were HIV infected. Intravenous aqueous penicillin G was administered in 69 (58%), intramuscular benzathine penicillin in 25 (21%) and other antibiotics, mainly due to allergy, in three (3%) patients. Treatment allowed a visual improvement of –0.22 logMAR (gain of five lines on Snellen chart) after a mean follow-up period of 19 months. CONCLUSION: Syphilis can manifest with a widely diversified array of ocular presentations, especially uveitis and optic nerve involvement. Therefore it is primordial to keep this diagnosis in mind when facing high-risk patients with ocular symptoms. It is of utmost importance that clinicians improve rates of lumbar puncture, HIV screening and intraveinous penicillin treatment when managing ocular syphilis. DISCLOSURES: All authors: No reported disclosures.